Knowledge levels of health professional working in Ethiopia toward disaster preparedness, systematic review and meta-analysis - Sheganew Fetene Tassew; Temesgen Ayenew; Tadila Dires Nega; Berihun Bantie; Dejen Getaneh Feleke (Elsevier, 2024)
Back groundA disaster is defined by the World Health Organization as a sudden ecological phenomenon of sufficient magnitude to necessitate outside help. Health institutions play an important part in the healthcare system during a disaster by providing critical medical care to their communities. It is critical that health professionals are prepared for catastrophes in order to protect themselves and the community. Method: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, we systematically reviewed and meta-analyzed articles from PubMed, Google Scholar and other electronics database that investigated levels of health professional knowledge toward disaster preparedness. To assess the pooled national health professional knowledge level, a weighted inverse variance random-effects model was used. Result: For the analysis, a total of 7 studies with a total of 1579 participants were used. In Ethiopia, the pooled good knowledge levels of health professional toward disaster preparedness was 48.58% (95% CI: 43.43, 53.73), implying that 48.58% of health professionals had good knowledge towards disaster preparedness. Based on the included studies positive predictive factors associated with health professional good knowledge of disaster preparedness include being a nursing professional, past experience in big disaster management, disaster training, and disaster simulation practice. Conclusion: In conclusion, only 48.58% of health professionals had good understanding of disaster preparedness, while the remaining 51.42% lacked disaster preparedness knowledge. The government, educational institutions, and non-governmental organizations should place a special emphasis on preparing health professionals for disaster management by providing training, sharing experience, and incorporating disaster management training into health professional curricula in their higher education programs.